Immunogenicity and protective efficacy of an inactivated Newcastle disease virus vaccine encapsulated in poly-(lactic-co-glycolic acid) nanoparticles - B.S. Ananda Kumar; Sivasankar Panickan; Suresh Bindu; Vimal Kumar; Saravanan Ramakrishnan; Sonal Saxena; Sameer Shrivastava; Satyabrata Dandapat (Poultry Science, 2023)
ABSTRACT: An immunization experiment was conducted in specific pathogen-free chickens with the inactivated Newcastle disease virus (NDV) vaccine encapsulated in the poly-(lactic-co-glycolic) acid (PLGA) nanoparticles (NP) to evaluate its immunogenicity and protective efficacy. The NDV vaccine was prepared by inactivating one virulent Indian strain of NDV belonging to Genotype VII by using beta-propiolactone. PLGA nanoparticles encapsulating inactivated NDV were prepared by the solvent evaporation method. Scanning electron microscopy and zeta sizer analysis revealed that the (PLGA+NDV) NP were spherical, with an average size of 300 nm, having a zeta potential of -6 mV. The encapsulation efficiency and loading efficiency were 72% and 2.4%, respectively. On immunization trial in chicken, the (PLGA+NDV) NP induced significantly (P < 0.0001) higher levels of HI and IgY antibodies with the peak HI titer of 28 and higher expression of IL-4 mRNA. The consistency of higher antibody levels suggests slow and pulsatile release of the antigens from the (PLGA+NDV) NP. The nano-NDV vaccine also induced cell mediated immunity with higher expression of IFN-γ indicating strong Th1 mediated immune responses in contrast to the commercial oil adjuvanted inactivated NDV vaccine. Further, the (PLGA+NDV) NP afforded 100% protection against the virulent NDV challenge. Our results suggested that PLGA NP have adjuvant potential on induction of humoral as well as Th1 biased cell mediated immune responses and also enhanced protective efficacy of the inactivated NDV vaccine. This study provides an insight for development of PLGA NP based inactivated NDV vaccine using the same genotype circulating in the field as well as for other avian diseases at exigencies.